Advances in photodynamic therapy for the treatment of hilar biliary tract cancer. (December 2010) - Kiesslich, Tobias; Neureiter, Daniel; Wolkersdörfer, Gernot W; Plaetzer, Kristjan; Berr, Frieder
The prognosis of patients with nonresectable hilar biliary tract cancer (hBTC) is poor. Responsiveness to chemotherapy or radiochemotherapy is moderate at best, and patients are at a high risk of dying early from complications of local tumor infiltration (e.g., cholestasis, septic cholangitis, empyema or liver failure) rather than systemic disease. Therefore, palliative local therapy for the prevention of tumor complications plays a central role and still yields the longest survival times. Photodynamic therapy (PDT) is a local-ablative, tumor tissue-specific treatment currently representing the standard of care for nonresectable hBTC. Throughout the literature, PDT plus biliary drainage achieves median survival times in the range of 9–21 months (average 14–16 months), compared with approximately 6 months for drainage only. This article summarizes the recent advances in preclinical and clinical experience of PDT for hBTC, including experimental in vitro and in vivo studies, clinical studies and an overview of the ongoing clinical trials.